Efficient separation of tanshinones by polyvinylpyrrolidone‐stabilized graphene‐modified micellar electrokinetic chromatography. Issue 23 (29th September 2015) - Yang, Hua; Ding, Yao; Gao, Wen; Qi, Lian‐Wen; Cao, Jun; Li, Ping
Abstract : In this work, a PVP‐stabilized graphene was used in MEKC for the separation of tanshinones. Seven structurally similar tanshinones were studied, that is, tanshinone IIB, dihydrotanshinone I, tanshinone I, cryptotanshinone, 1, 2‐dihydrotanshinone I, miltirone, and tanshinone IIA. To achieve optimal conditions, graphene concentration, sample solvent composition, SDS concentration, 2‐propanolconcentration, and buffer pH were investigated. At a separation voltage of 30 kV and a 41.5 cm effective length fused‐silica capillary, good resolution within 12 min was performed using 10 mM borate buffer (pH 9.3) containing 30 mM SDS, 10% v/v 2‐propanol and 6 μg/mL graphene. The method was validated in terms of linearity ( r 2 > 0.9970), intra‐ and inter‐day precision were less than 3.56 and 4.83%, respectively. The proposed method was then successfully applied to Danshentong capsule, an herbal preparation from Salvia miltiorrhiza . Our results indicated the high separation efficiency of PVP‐stabilized graphene provided new opportunities for the analysis of complex samples.